Pelatihan Penggunaan Model Dinamik Powersim Studio Untuk Dokumen Kajian Lingkungan Hidup Strategis (KLHS) dalam Rencana Pembangunan Jangka Panjang Daerah (RPJPD) - Auldry F. Walukow; Yulius Mataputun (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
In Indonesia, strategic environmental assessment (KLHS) documents are crucial for developing long-term regional plans (RPJPD). SEA provides the foundation for developing regional policies and activities so that development can be carried out sustainably. The goal of this training is to teach the use of Powersim Studio's dynamic model for preparing KLHS RPJPD documents in Jayapura City. The training is designed for communities directly involved in regional development policies and activities. In June 2024, the training was conducted for 12 Jayapura Regency Environment Agency civil servants using Powersim Studio tools. Results showed increased simulation capabilities regarding water and food carrying capacities and Sustainable Development Goal indicator scenarios from 2025 to 2045. Participants gained an understanding of how to support performance and long-term needs simulations.